(untitled) (AmS-Skrifter, 2019)
The chapter details research conducted as part of the BEVARES (Biological EnVironmental and Archaeological interdisciplinary RESearch on life-course, material and materiality in human depositions) programme at the Museum of Archaeology, University of Stavanger. Initially an attempt to gain a better understanding of the museum’s archived bone material, as well as evaluate the information potential of analysing/re-analysing the (primarily) burnt/cremated bone within that material, the work moved towards identifying evidence for the young and the old in the burial record. This led to an interest in the intersection of the young and the old in the burial record as a potential new area of archaeological study. The current project focuses on burials of these two groups. Bronze and Iron Age bone assemblages from Rogaland county, southwestern Norway, are included in the study. A variety of factors were quantified, but the age of the individuals and the number of people per burial are of primary relevance here. Initial results have revealed some interesting trends – the number of sub-adults in the burial record is much greater than previously thought, and the mortality pattern seen in Rogaland is quite different from that evident in comparable material from Eastern Norway. The occurrence of young and old individuals in the same burial context does not appear to be a common phenomenon.